If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying u + 15 = 2u + -26 Reorder the terms: 15 + u = 2u + -26 Reorder the terms: 15 + u = -26 + 2u Solving 15 + u = -26 + 2u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-2u' to each side of the equation. 15 + u + -2u = -26 + 2u + -2u Combine like terms: u + -2u = -1u 15 + -1u = -26 + 2u + -2u Combine like terms: 2u + -2u = 0 15 + -1u = -26 + 0 15 + -1u = -26 Add '-15' to each side of the equation. 15 + -15 + -1u = -26 + -15 Combine like terms: 15 + -15 = 0 0 + -1u = -26 + -15 -1u = -26 + -15 Combine like terms: -26 + -15 = -41 -1u = -41 Divide each side by '-1'. u = 41 Simplifying u = 41
| 4(m-85)=28 | | -3=5(m+2) | | 2x-4=-3x+5 | | 4p-55=2p-19 | | -9x+3.2=-6x+3.8 | | F(0)=-5x+7 | | 7+5+x=9+3 | | v=5v-100 | | x+(3x+6)+2x=180 | | x+.6x=4202.38 | | F(-1)=-5x+7 | | -2(3t-2)+3t=4t-7 | | 9+3=x-5 | | 8y-2=17y+52 | | 3b+41=b+59 | | 2x+6=4+7x | | 5x-4=z+16 | | -3(2t-3)+2t=8t-8 | | 26=2+4t | | q-9=6q-69 | | 12x+83=215 | | 2w-79=w-28 | | -6.8=5.2-3y | | 2.7-4.5=3.6-9 | | y=x+2x-x+1 | | 4(3n+4)=8(4n+7)+9 | | e^3x+9=1 | | -6t-5=-29 | | 2c=c+13 | | 2c=c+w | | 42-6y= | | Log(x-5)+log(x)=log(36) |